The social media leads to socialism. Issue 4 (9th November 2015) - Gomez Farias, Hannah; Paskor, Ann; Block, Walter E.
Abstract : Purpose: – The purpose of this paper is to trace the relationship between social media and socialism. Design/methodology/approach: – The design of this paper is to articulate what is socialism and social media. We trace the relationship between the two based on quotations and citations between these two separate universes of discourse. Findings: – Social media leads to socialism; this is the most unsophisticated understanding of economics, and pretty much anyone can take part in this mode of communication. The economically illiterate excoriate capitalism, but they fail, utterly, to distinguish between the crony capitalism, which really does exploit workers and the poor, from laissez-faire capitalism, which is the last best hope for humanity to prosper and even to survive. Originality/value: – There is great originality in this paper because there is no other extant study that attempts to explain social media and socialism in terms of each other.